The Impact of Role Play Method in Enhancing Communication Skills in Early Childhood: Enhancing Early Childhood Communication Through Role Play - Yola Marcelita Dwi Putri; Isabella Hasiana (Primary Education Insight, 2025)
Communication skills are an important aspect of a child's development that affects their ability to interact with their social environment. The role play method is known as an effective approach to develop these skills as it allows children to express themselves freely through various roles they play. This study aims to examine the effect of role play method in enhancing communication skills in early childhood. This research uses an experimental design with a control group, where the experimental group is treated with role play activities, while the control group receives conventional learning. The subjects of this research were five to six years old children spread across several kindergartens, a total of 60 students. The instruments used in this study are observations and interviews to measure changes in communication skills before and after treatment. The results show that the role play method has a significant positive impact on improving communication skills in early childhood. Children who participated in role play activities showed improvement in speaking, listening, and interacting with their peers. This study concludes that the role play method can be an effective strategy for improving communication skills in early childhood, and thus can be applied in early childhood education institutions. The results of this study are expected to contribute to the development of more interactive and creative learning methods to support children's communication skill development.